Pengaruh Brand Image dan Brand Trust terhadap Loyalitas Konsumen Sepatu Converse melalui Kepuasan Konsumen sebagai Variabel Intervening (Studi pada Mahasiswa Universitas Diponegoro) - Rianto, Cezzare Reinaldho; Widayanto, Widayanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
The rapid development of globalization has become unavoidable. This development makes business competition tougher, one of which is a fashion business. The competition for footwear products is one that has a high level of competition in the Indonesian fashion world. Converse is one product that has a large market share in Indonesia. Converse itself is a company originating from America. Converse offers a variety of casual shoe designs to consumers such as All Stars and others. This type of research is explanatory research, using a questionnaire as a method of data collection. The purpose of this study was to determine the direct effect between Brand Image and Brand Trust variables on Consumer Loyalty, and the indirect effect of Brand Image and Brand Trust on Consumer Loyalty through Consumer Satisfaction on Converse consumers who are students at Diponegoro University. The research method used is the Non-Probability Sampling technique with the Snowball Sampling method. Samples collected as many as 100 respondents were divided equally according to the faculty using Stratified Random Sampling and selected based on consideration. The study uses a Partial Least Square analysis technique, which is estimated by the WarpPLS 6.0 program. Based on the analysis of data processing by WarpPLS, it is explained that the results of the test have a direct effect on the research model showing positive and significant results. Indirect effect test on the research model also shows positive and significant results. Researchers provide advice to the Converse based on the recapitulation value that is below the average given by respondents in the assessment indicators, namely providing more outlets in various regions of Indonesia, adding product variants such as product models and colors, improving the cashier system and salespeople by providing small change. as well as providing more information related to Converse products, offering member cards that provide special discounts and providing the latest information related to products, leveling out outlets that can exchange non-conforming products, and improving product experience to suit their expectations.